THE PREVENTION OF ROTAVIRUS INFECTION: THE MODERN VIEW OF THE POSSIBILITY - T. A. Grechukha; D. A. Novikov; N. E. Tkachenko; L. S. Namazova-Baranova (LLC "Diagnostics and Vaccines", 2015)
Rotavirus is a major public health problem in all countries. The incidence of rotavirus infection is growing steadily in the Russian Federation and over the past 10 years increased by 7 times, amounting to 72 cases per 100,000 in 2010. The rotavirus vaccine was registered in the Russian Federation in 2012 and successfully applied from 2013. The vaccine used for more than 8 years and have enough experience on the efficacy and safety. Different foreign investigations have shown the herd immunity of the vaccine. The authors present data about the effectiveness and safety of vaccines, established during clinical studies of the foreign scientists.